The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1063/1.329320
|View full text |Cite
|
Sign up to set email alerts
|

Metal-polymer interfaces: Adhesion and x-ray photoemission studies

Abstract: The interfaces formed by evaporating copper, nickel, and chromium layers on polystyrene, polyvinyl alcohol, polyethylene oxide, polyvinyl methyl ether, polyvinyl acetate, and poly~ethyl methacrylate have been studied with x-ray photoemission spectroscopy (XPS). The adhesIOn strengths of the metal films to the polymers were measured by a tensile-pull test. At submonolayer coverages of the metals, the peak positions and widths of the metallic electron core levels measured with XPS vary significantly from one pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(72 citation statements)
references
References 27 publications
3
69
0
Order By: Relevance
“…[22] However, the conditions of deposition of the metal onto the PDMS surface may influence the characteristics of the deposited film. Studies on the interaction of evaporated Au with a low surface free energy substrate (Teflon AF) revealed a very small condensation coefficient of the incoming Au atoms on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…[22] However, the conditions of deposition of the metal onto the PDMS surface may influence the characteristics of the deposited film. Studies on the interaction of evaporated Au with a low surface free energy substrate (Teflon AF) revealed a very small condensation coefficient of the incoming Au atoms on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The pullup test provides a superior measure of adhesion, in comparison with other methods such as peel testing, for polymer-metal interfaces. [32] In this work, we examine the effect of ATmaP and other flame-based surface-treatment processes on PP surface properties that are relevant to adhesion. XPS and ToF-SIMS are used to examine changes in surface chemistry and pull-up tests are used to characterise adhesion strength.…”
Section: Introductionmentioning
confidence: 99%
“…The peeled-copper foil also showed some characteristics IR peak of polyurethane, such as C¼ ¼O stretching at 1725 cm À1 (free) and 1700 cm À1 (hydrogen bonded). Many researchers have reported that the adhesion strength between polymer and metal could be enhanced significantly by incorporation of nitrogen-or oxygen-containing functionalities into the polymer [30][31][32] ; but this hypothesis is contradicted by the polyurethane/Cu system. Further, chemical treatment of Cu with amino acids or silane solution appeared to be necessary to reach desirable adhesion strength.…”
mentioning
confidence: 95%